2019
DOI: 10.21475/ajcs.19.13.12.p2003
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus spp. as plant growth-promoting bacteria in cotton under greenhouse conditions

Abstract: The use of plant growth-promoting bacteria (PGPB) is a promising alternative method to improve plant efficiency in the utilization of chemical fertilizers, enabling a reduction of fertilizer application on crops. This study aimed to evaluate the potential of ten Bacillus strains (eight B. subtilis, one B. velezensis and one B. amyloliquefaciens) to promote growth in cotton plants under greenhouse conditions. The experiment was performed in a completely randomized design with 11 treatments and five replicates u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 22 publications
1
28
0
2
Order By: Relevance
“…This is due to the particular conditions of use of each microbial group [7]. The application of biostimulants makes it possible to reduce the use of chemicals that have generated a serious environmental impact [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the particular conditions of use of each microbial group [7]. The application of biostimulants makes it possible to reduce the use of chemicals that have generated a serious environmental impact [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms (bacteria and fungi) used in this study belong to the collection of the Laboratory of Soil Microbiology, UNESP, Campus of Jaboticabal (Table 1) and were selected for presenting growth-promoting characteristics such as phosphorus solubilization, biological nitrogen fixation, and indole acetic acid production (Baron et al, 2018;Diaz et al, 2019;Milani et al, 2019). The microorganisms used in the study were pre-inoculated in Petri dishes containing nutrient agar for bacteria and potato dextrose agar for fungi.…”
Section: Microorganisms and Inoculant Preparationmentioning
confidence: 99%
“…Another nutrient that plays an important role in plants is phosphorus, which forms biological molecules; however, its low availability and high fixation in the soil are problems that lead to deficiencies; thus, phosphorus is a limiting factor for plant growth (Anand et al, 2016). In view of the above, the nutritional requirements for cotton production can be addressed by using plant growth-promoting microorganisms (Diaz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the use of plant growth-promoting microorganisms as inoculants is a viable strategy in current agricultural production systems (Romero-Perdomo et al, 2017;Numan et al, 2018;Diaz et al, 2019); therefore, the search for new microorganisms must be constant to face current and future problems in cotton crops.…”
Section: Introductionmentioning
confidence: 99%